CLUSTERING OF BALI CATTLE STALLING MANAGEMENT AT SIMANTRI IN BADUNG REGENCY - Suputra, Gusde Wahyu Krisna; Sampurna, I Putu; Nindhia, Tjok Sari; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2019)
Clustering study of bali cattle housing management in integrated farming system (Simantri) in Badung Regency aims to find out the components of bali cattle that have not been intensively carried out in group farmers (Gapoktan) in Badung Regency and to find out which Gapoktan has not conducted the Bali cattle intensive system in Simantri in Badung Regency. Sampling of bali cattle housing management was carried out by saturated sampling technique. The data obtained were analyzed by Hierarchical clusters with dendogram cluster plot with intensive, semi-intensive, and extensive identifying variables. The results showed that 42 out of 50 Simantri in Gapoktan in Badung District have intensive management, stalling management components which are mostly carried out intensively include: cage roofs, food stalls, drinking places, cages, circumstances around the cage, and cage cleaning. There are 8 Simantri whose stalling management is still semi-intensive. The housing management component that is still applied semi-intensively was cage cleanliness. Counseling for Simantri members is needed to improve cage cleaning management.